Hidrogeoquímica e fluxos subterrâneos em área cárstica na porção central do Estado de Minas Gerais, Brasil - Débora Maria Diniz Barbosa (2024)
In the central portion of the state of Minas Gerais, Brazil, carbonate and siliciclastic rocks from the base of the Bambuí basin outcrop, belonging to the Sete Lagoas and Serra de Santa Helena formations, which were deposited over granite-gneissic migmatitic rocks of the Belo Horizonte Complex. The studied region encompasses the northern portion of the Lagoa Santa Karst Environmental Protection Agency (EPA) and adjacent areas to the west, hosting several speleological, archaeological, and paleontological sites, as well as relevant karst-fissure aquifers, responsible for a large portion of the urban and industrial water supply in the area. With the advancement of hydrogeological knowledge in the area, indications were noted that the recharge of the aquifers present in the EPA could originate from external contribution areas. Thus, this research aimed to evaluate the hydrogeological continuity between the adjacent region to the west and the northern portion of the Lagoa Santa Karst EPA, in order to identify if the current delimitation of the environmental conservation unit is sufficient to encompass the hydrogeological system of the entire area. For this purpose, different methodological techniques were used, such as hydrogeochemical analyses, dye tracer application, and electrical resistivity tests. Hydrogeochemical analyses reveal notable chemical differences between the waters from different aquifer units; however, they indicate a significant influence of the karstic aquifers on the other units, as all sampled waters were classified as bicarbonate, with 87% being calcium bicarbonate. The enrichment of calcium and bicarbonate ions from west to east indicates underground flow in that direction. Dye tracer application in a sinkhole to the west of the EPA and monitoring near the Bom Jardim spring, located in the central-southern portion of the conservation unit, confirmed the external contribution to the EPA through the underground medium. Finally, electrical resistivity tests allowed the identification of karst conduits preferably flowing from west to east, responsible for conducting water to the surface at spring points. From the proposition of the contribution areas of important karst springs located on the western edge of the Lagoa Santa Karst EPA, it is necessary to expand the EPA or create a new environmental conservation unit in the region, in order to encompass as much as possible of the relevant, yet vulnerable, local karst hydrogeological system.